Penguatan Nilai Kedisiplinan Anak Usia Dini - Amalia (Jambura Early Childhood Education Journal, 2025)
Abstract __________________________________________________________ This study aims to describe more deeply about strengthening the value of children's discipline, the second goal is to describe the supporting factors and support the value of children's discipline in the Permata Bunda Klapanunggal play group. This research uses an approach with a descriptive type of research. This research data was collected through interviews with teachers, principals, parents, children, observation and documentation. The data collected were analyzed descriptively qualitatively. The validity of the research data was tested again by using additional participation, observation, and triangulation. The results of the study include: 1) Strengthening the value of early childhood discipline has been carried out in the Permata Bunda Klapanunggal play group. carried out starting from planning, implementation, and evaluation. 2) The process of strengthening the value of children's discipline in the Permata Bunda Klapanunggal Play group through preventive, repressive, and curative stages. 3) Supporting factors that support the value of early childhood discipline include: lattering to familiarize children with discipline, and adequate facilities and infrastructure in schools. Factors inhibiting the value of discipline include: lack of cooperation from parents, differences in parenting patterns for students and differences in habituation in different home and school environments. Abstrak ______________________________________________________________ Penelitian ini bertujuan untuk mendeskripsikan lebih mendalam mengenai penguatan nilai kedisiplinan anak usia dini, tujuan kedua untuk mendeskripsikan faktor penghambat dan pendukung penguatan nilai kedisiplinan anak usia dini di kelompok bermain Permata Bunda Klapanunggal. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data penelitian ini dikumpulkan melalui wawancara dengan guru, kepala sekolah, wali murid, anak-anak, observasi, dan dokumentasi. Data yang terkumpul dianalisis secara deskriptif kualitatif. Data hasil penelitian diuji kembali keabsahannya dengan menggunakan perpanjangan keikutsertaan, ketekunan pengamatan, dan triangulasi. Hasil penelitian meliputi: 1) Penguatan nilai kedisiplinan anak usia dini sudah dilakukan di kelompok bermain Permata Bunda Klapanunggal. Dilakukan mulai dari perencanaan, pelaksanaan, evaluasi. 2) Proses penguatan nilai kedisiplinan anak di Kelompok Bermain Permata Bunda Klapanunggal melalui tahap preventif, represif, dan kuratif. 3) Faktor pendukung penguatan nilai kedisiplinan anak usia dini meliputi: tulisan pembiasaan tentang kedisiplinan anak, dan sarana dan prasarana yang memadai di sekolah. Faktor penghambat penguatan nilai kedisiplinan meliputi: kurangnya kerjasama dari orang tua, perbedaan pola asuh orang tua pada peserta didik dan perbedaan pembiasaan di lingkungan rumah dan sekolah yang berbeda. © 2023 Universitas Negeri Gorontalo Under the license CC BY-SA 4.0